Physiological responses, fatigue and perception of female soccer players in small-sided games with different pitch size and sport surfaces - Jorge López-Fernández; Javier Sánchez-Sánchez; Sergio Rodríguez-Cañamero; Esther Ubago-Guisado; Enrique Colino; Leonor Gallardo (Termedia Publishing House, 2018)
The aim of this research was to evaluate the influence of game surface and pitch size on the physiological responses, jump performance and perceptions of sub-elite female soccer players playing four-a-side games. Sixteen sub-elite female soccer players were divided into four groups of four players each. Three small-sided games (SSGs; pitch size: 400 m 2 , 600 m 2 and 800 m 2 ) were played on three surfaces (dirt [DT], artificial turf [AT] and natural grass [NG]). Players' heart rate (HR) was monitored during each game. Before and after each SSG, participants performed two counter-movement jumps (CMJs) and answered a questionnaire based on visual analogue scales (VASs) to indicate their perception of the effort required on each surface. DT obtained lower outputs for most variables. In the SSG 600 mean HR was higher on NG than AT (+3.31 %HR max ; p = 0.029), but players' overall satisfaction with both surfaces was similar (p>0.05). The SSG 400 received the lowest ratings for most variables, whereas the SSG 600 resulted in higher mean HR than SSG 800 [NG (+9.14 b.p.m.; p = 0.001); AT (+7.32 b.p.m.; p = 0.014)]. No surface differences in CMJ performance were found. In conclusion, a higher internal load can be achieved on NG, whereas DT is not recommended for playing soccer. Moreover, the internal load on players in SSGs can be controlled by manipulating pitch size, but over-large pitches may entail a reduction in the physiological profile of female soccer players.